2016
DOI: 10.1111/jce.12971
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Evaluation of Biotronik Linox and Linoxsmart Implantable Cardioverter Defibrillator Leads

Abstract: Linox and Linox(smart) ICD leads are safe, reliable and infrequently associated with lead-related AEs. Additionally, estimated cumulative survival probability is clinically acceptable and well within industry standards. Ongoing data collection will confirm the longer-term safety and performance of the Linox family of ICD leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
2
11
1
Order By: Relevance
“…Linox S/SD leads are no longer commercially available and have been replaced over recent years with the Linox smart models that have additional silicone‐based outer coating, Silglide®, designed to improve gliding characteristics and reduce friction within the introducer and between the leads. A recent analysis of data from large prospective postmarket registries, GALAXY and CELESTIAL, involving 3,933 Linox family ICD leads implanted in 3,840 patients at 146 U.S. centers, did not confirm the above concerns . In this analysis, based upon prospectively defined and independently adjudicated lead‐related adverse events, both Linox and Linox smart models showed clinically acceptable performance with survival estimates of 96.3% at 5 years (Linox) and 96.6% at 4 years (Linox smart) .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Linox S/SD leads are no longer commercially available and have been replaced over recent years with the Linox smart models that have additional silicone‐based outer coating, Silglide®, designed to improve gliding characteristics and reduce friction within the introducer and between the leads. A recent analysis of data from large prospective postmarket registries, GALAXY and CELESTIAL, involving 3,933 Linox family ICD leads implanted in 3,840 patients at 146 U.S. centers, did not confirm the above concerns . In this analysis, based upon prospectively defined and independently adjudicated lead‐related adverse events, both Linox and Linox smart models showed clinically acceptable performance with survival estimates of 96.3% at 5 years (Linox) and 96.6% at 4 years (Linox smart) .…”
Section: Discussionmentioning
confidence: 65%
“…A recent analysis of data from large prospective postmarket registries, GALAXY and CELESTIAL, involving 3,933 Linox family ICD leads implanted in 3,840 patients at 146 U.S. centers, did not confirm the above concerns. 21 In this analysis, based upon prospectively defined and independently adjudicated lead-related adverse events, both Linox and Linox smart models showed clinically acceptable performance with survival estimates of 96.3% at 5 years (Linox) and 96.6% at 4 years (Linox smart) . However, the incidence of functionally silent conductor externalization remains unknown.…”
Section: Biotronik Linox Icd Lead Familymentioning
confidence: 87%
“…Of note are the excellent survival rates of the Linox S and SD leads (97% and 97.8% at 5 years, respectively), described in Biotronik's product performance report in January 2016 and of the Linox Smart SD lead, published in January 2017, with survival rates of 98.3% at 5 years. Likewise, the results of the Biotronik Galaxy and Celestial registries, with a mean follow‐up of 2.3 years for Linox Smart leads, report a lead failure rate of 2.2% at 3 years, which underestimates the true performance of these leads in terms of the development of oversensing, which mostly develops from the third year onward (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies investigated the survival of the Linox model. Good and colleagues reported similar estimated cumulative survival probability rates for both Linox models. In our cohort, the follow up of Linox model (63.7 ± 24.1 months) was significantly longer than Linox Smart model (31.8 ± 14.7 months), and the survival probability of Linox model ICD was not different compared to Linox Smart model during 63 months follow up.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies reported that the Linox ICD leads are safe. Good and colleagues reported 96.3% survival probability at 5 years, a clinically acceptable rate. Conversely, many others showed early failure of the Linox ICD leads.…”
Section: Discussionmentioning
confidence: 98%